PENGARUH ONLINE TRAVEL AGENT TERHADAP PEMESANAN KAMAR DI HOTEL MUTIARA MALIOBORO YOGYAKARTA - Hendriyati, Lutfi (Sekolah Tinggi Pariwisata AMPTA, 2019)
Technological developments and can changes in the mind and desires of guests in booking hotel rooms. Online travel agents are one of the most advanced products that are currently booming, and also for changes room reservation to be direct or go shows switching to using online travel agents. The purpose of this study was to know information why the guest booking room directly going to online travel agents, in order to improve e-commerce effort of services to maintain guest while still choosing Mutiara Malioboro Hotel Yogyakarta as a place to stay. Research is an online travel agent that can increase hotel occupancy rates because they are accessible, efficient and effective at competitive prices, as well as hotel costs with sales costs, fees and employee usage fees. Management support in OTA is also needed in an effort to increase the number of orders through OTA.